Jordan School Feeding : SABER Country Report 2016 - World Bank Group (World Bank, Washington, DC, 2017)
This report presents an assessment of school feeding policies and institutions that affect young children in Jordan. The analysis is based on a World Bank tool developed as part of the Systems Approach for Better Education Results (SABER)an initiative that aims to systematically assess education systems against evidence-based global standards and goodpractice to assist countries in reforming their education systems for proper learning for all. School feeding policies are a critical component of an effective education system, given that children's health and nutrition impact their school attendance, ability to learn, and overall development. A school feeding program is a specific schoolbasedhealth service, which can be part of a country’s broader school health program, and often a large amount ofresources is invested in a school feeding program. SABER–School Feeding collects, analyzes, and disseminates comprehensive information on school feeding policies around the world. The overall objective of the initiative is to helpcountries design effective policies to improve their education systems, facilitate comparative policy analysis, identify keyareas to focus investment, and assist in disseminating good practice.In late 2013, the World Food Programme (WFP) launched a Revised WFP School Feeding Policy that incorporates SABER–School Feeding. The revised policy requires every WFP country office with a school feeding component to undertake apolicy dialogue with the Education Sector in the country as part of capacity building activities. WFP decided to use SABER–School Feeding as one of their policy tools to guide the policy dialogue and to assess in a more systematic way the transition of school feeding programs to national ownership and/or the strengthening of national school feeding programs. WFP will integrate this tool into their project preparation from 2015 onwards. There are five core policy goals form the basis of an effective school feeding program. The first goal is a national policy framework.The second policy goal for school feeding is financial capacity.The third policy goal is institutional capacity and coordination.The fourth policy goal is sound design and implementation.The last policy goal is community roles—reaching beyond schools.